2022
DOI: 10.1177/20503121221081069
|View full text |Cite
|
Sign up to set email alerts
|

The association between folic acid supplementation and congenital heart defects: Systematic review and meta-analysis

Abstract: Introduction: Various trial and epidemiological studies consistently documented the association between maternal folic acid supplementations and neural tube defects. However, existing literatures revealed inconclusive findings about maternal periconceptional folic acid supplementations and the risk of congenital heart defects. Thus, the current systematic review and meta-analysis was aimed to estimate the pooled association between maternal periconceptional folic acid supplementations and congenital heart defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…This study showed that clients who had never taken folic acid tablet were more likely to develop congenital anomalies, or clients who had taken folic acid tablet were less likely to develop congenital anomalies compared to those who haven't taken folic acid. Similarly a study states that maternal preconception folic acid supplementation was significantly associated with the risk of congenital anomalies [55]. A study shows a robust estimate of the positive association between maternal folate supplementation and a decreased risk of congenital anomalies [56].…”
Section: Plos Onementioning
confidence: 97%
“…This study showed that clients who had never taken folic acid tablet were more likely to develop congenital anomalies, or clients who had taken folic acid tablet were less likely to develop congenital anomalies compared to those who haven't taken folic acid. Similarly a study states that maternal preconception folic acid supplementation was significantly associated with the risk of congenital anomalies [55]. A study shows a robust estimate of the positive association between maternal folate supplementation and a decreased risk of congenital anomalies [56].…”
Section: Plos Onementioning
confidence: 97%
“…Folic acid has been linked with a reduction in the risk for neural tube defects (NTD) (Czeizel 1998;Wolff et al 2009;van Gool et al 2018) and other birth defects such as congenital heart issues Erickson 2000, 2003;Czeizel, Vereczkey, and Szabo 2015;Jahanbin et al 2018;van Beynum et al 2010;Wondemagegn and Afework 2022).…”
Section: Why Is Folic Acid Important For Women Who Can Become Pregnant?mentioning
confidence: 99%
“…Whether maternal periconceptional FA supplementation could reduce the risk for CHD in the offspring remains controversial. 40 41 Wang et al 42 found that maternal periconceptional supplementation with FA or multiple micronutrients containing FA seems to decrease the risk for CHD in offspring by analysing 63 969 cases drawn from two standardised network information systems. A published article 43 using data from the CBCS suggested that there is no effect of FA and/or multivitamin supplementation on the fetal risk of CHD.…”
Section: Possible Reasons and Comparison With Previous Studiesmentioning
confidence: 99%